Seminários Legislativos na ALMG: limites e possibilidades para o aperfeiçoamento da democracia representativa - Catherine Kelly Ornelas (2012)
This study is based on the premise that perfecting representative democracy requires the existence of new institutional spaces that are able to offer complimentary means so that citizens and actors from the civil society can express their needs and demands to their epresentatives during the time between elections. Thus, its consideredthat the Legislative Seminars held in the Minas Gerais Legislative Assembly have a promising format, allowing for the possibility of a positive influence on the responsiveness of the legislators of Minas Gerais and on the control the electorate has over them. Therefore, its an innovation that can contribute for the improvement of the quality ofrepresentation and, consequently, of the democracy in Minas Gerais. Twenty years after its creation, the Legislative Seminars continue to undergo modifications of their formal structure. With this in mind, this study presents and analyzes the main changes done since 1991 as well as their results, with the object of identifying factors that can, on their own or combined, influence the type and the quality of the results achieved. From this more general analysis, comes the case study of the seminar Poverty and Inequality A More Equal Minas, from 2011, which stands out because of the amplitude of the results and the impact over the public policies on the area. The event produced a large number of amendments to the Multiannual Plan for Government Action 2012-2015 (in Portuguese,PPAG) and the Annual Budget Law (in Portuguese, LOA). This result is explained by the combination of two factors: (a) the strategic change of submitting the proposals from the Final Document of the event to be debated in the Public Hearings of the PPAG, held by the Commission of Popular Participation and the Commission of Finances and Budget of theMinas Gerais Legislative Assembly and (b) the favorable political context surrounding the debate on poverty and social inequality.